2012
DOI: 10.1016/j.jclepro.2012.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Toward an eco-innovative method based on a better use of resources: application to chemical process preliminary design

Abstract: International audienceChemical industries have the potential to become a driving force to introduce efficient production practices for reducing the negative impact on the environment. In order to meet these environmental challenges, innovation is a key factor in turning the concept of green growth into a reality through the development of eco-friendly technologies and sustainable production. Therefore, to accelerate and improve the design of eco-inventive solutions, new approaches must be created and adapted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 32 publications
0
35
0
1
Order By: Relevance
“…An eco-process innovation stands for new elements introduced into an organization's production system for producing eco-products (Negny et al, 2012). In general, eco-process innovation refers to the improvement of existing production processes or the addition of new processes to reduce environmental impact.…”
Section: Eco-innovation Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…An eco-process innovation stands for new elements introduced into an organization's production system for producing eco-products (Negny et al, 2012). In general, eco-process innovation refers to the improvement of existing production processes or the addition of new processes to reduce environmental impact.…”
Section: Eco-innovation Typesmentioning
confidence: 99%
“…Rennings (2000) suggested that innovation can be additive solutions (e.g., smokestack scrubbers) or be integrated into the production processes through substitution of inputs, optimization of production, and reclamation of outputs. As a result, eco-process innovation modifies the organization's operation processes and systems, decreases unit costs of production, produces new or significantly improved eco-products, and reduces environmental impacts (Negny et al, 2012).…”
Section: Eco-innovation Typesmentioning
confidence: 99%
“…• Always with the purpose of reducing the level of abstraction, Negny et al (2012) have proposed applying the physical, chemical, biological, geometrical effects or phenomenon as solutions because they are more concrete. This is performed thanks to a resources-oriented search to better exploit the resources encompassed in a system.…”
Section: Creative Methodsmentioning
confidence: 99%
“…Eco-process innovation is modifying the organization's operational processes and systems, decreases unit costs of production, produces new or significantly improved eco-products and reduces environmental impacts (Negny et al, 2012). Ecoprocess innovation happens if some output (product and service) can be produced with input as minimum as possible (Kemp & Pearson, 2007).…”
Section: Eco-innovationmentioning
confidence: 99%